A new approach for the determination of the drag coefficient from the upper ocean response to a tropical cyclone: a feasibility study - Zedler, Sarah; Kanschat, Guido (Journal of oceanography, 2012)
We seek to determine if a small number of measurements of upper ocean temperature and currents can be used to make estimates of the drag coefficient that have a smaller range of uncertainty than previously found. We adopt a numerical approach using forward models of the ocean’s response to a tropical cyclone, whereby the probability density function of drag coefficient values as a function of wind speed that results from adding realistic levels of noise to the simulated ocean response variables is sought.
First online: 30 December 2011
Gesehen am 26.01.2018